PEO-PAN-based polymer electrolyte membrane as well as preparation method and application thereof
By using PEO-PAN-based polymer electrolyte membrane in lithium-ion batteries and adding lithium salts, active fillers and acidic organic boric acid substances, the safety hazards of existing lithium-ion battery liquid electrolyte solutions and the problem of low conductivity at room temperature in solid electrolyte membranes are solved, and the effects of high conductivity and long cycle life are achieved.
Patent Information
- Application Number
- CN202411863950.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The liquid electrolyte of existing lithium-ion batteries has safety hazards because it contains flammable and volatile organic solvents. The conductivity of solid polymer active fillers is low at room temperature, so their use is limited.
The PEO-PAN-based polymer electrolyte membrane is used to increase the conductivity and mechanical strength of the membrane by adding lithium salts, active fillers and acidic organic boric acid substances.
The conductivity and mechanical strength of the PEO-PAN-based polymer electrolyte membrane are significantly improved, the critical current density of polyethylene oxide (PEO) organic-inorganic composite solid active filler is greatly improved, and the cycle time of lithium symmetric batteries is extended.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a PEO-PAN based polymer electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile phones, military, electric vehicles and other fields due to their advantages such as small size, light weight, high capacity and no memory effect.
[0003] Lithium-ion battery electrolytes are divided into liquid electrolytes and polymer active fillers. The advantage of the currently widely used liquid active fillers is high conductivity, but because they contain flammable and volatile organic solvents, they release flammable gases during the charging and discharging process. Especially under certain unconventional working conditions (such as high-power charging and discharging, overcharging and over-discharging, etc.), a large amount of heat will accelerate the generation of gas, leading to increased internal pressure of the battery, gas leakage, and even fire and explosion, thus posing serious safety hazards. Polymer active filler lithium-ion batteries are valued by researchers because of their safety, no leakage, low leakage current, and can be arbitrarily shaped. However, solid polymer active fillers (also known as polymer electrolyte membranes) have low conductivity at room temperature, and their use is limited. Summary of the invention
[0004] The invention provides a PEO-PAN based polymer electrolyte membrane and a preparation method and application thereof. The PEO-PAN based polymer electrolyte membrane of the invention has high electrical conductivity.
[0005] The present invention provides a PEO-PAN based polymer electrolyte membrane, comprising the following components: PEO (polyethylene oxide), PAN (polyacrylonitrile), lithium salt, active filler and acidic organic boric acid substances;
[0006] The mass ratio of PEO to lithium salt is (1-20):1;
[0007] The mass ratio of PEO to PAN is (1-25):1;
[0008] The mass ratio of the total mass of PEO and lithium salt to the mass of the active filler is (1-40):1;
[0009] The mass ratio of the total mass of the PEO and the lithium salt to the acidic organic boric acid substance is (1-40):1.
[0010] Preferably, the lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
[0011] Preferably, the active filler includes lithium element.
[0012] Preferably, the active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium yttrium chloride, lithium zirconium chloride, lithium tantalum chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphate, lithium aluminum germanium phosphide and lithium phosphorus sulfur chlorine.
[0013] Preferably, the acidic organic boronic acid substances include 4-(morpholine-4-carbonyl)phenylboronic acid, 4-pyridineboronic acid, 3-alkynephenylboronic acid, 4-methyl-1-naphthaleneboronic acid, catecholborane, 3-pyrrolidineboronic acid, benzofuran-2-boric acid, dibenzofuran-4-boric acid, 2-benzylthiophenylboronic acid, 3-aminophenylboronic acid hemisulfate, cyclohexene-1-ylboric acid, tetrahydropyran-4-boric acid, 3-mercaptophenylboric acid, borane-N,N-diethylaniline, pyrimidine-4-boric acid, pyrazine-2- Boric acid, selenophene-2-boric acid, m-aminophenylboronic acid, 2-anthraceneboric acid, 2-cyanophenylboronic acid, 4-(piperidine-1-carbonyl)phenylboronic acid, indazole-7-boric acid, 1H-pyrazole-4-boric acid, trifluoromethanesulfonate dibutylboronic acid, 4-methylthiophene-2-boric acid, isoquinoline-6-boric acid, 4-benzyloxyphenylboric acid, 5-bromo-2-thiopheneboric acid, 6-ethoxy-2-naphthaleneboric acid, 2-methyl-4-pyridineboric acid, bis-valeryldiboronic acid and 1H-imidazol-2-ylboronic acid hydrochloride.
[0014] The present invention also provides a method for preparing the PEO-PAN based polymer electrolyte membrane according to the above technical solution, comprising the following steps:
[0015] The PEO, PAN, lithium salt, active filler, acidic organic boric acid substance and organic solvent are mixed and then film-formed to obtain the PEO-PAN based polymer electrolyte membrane.
[0016] Preferably, the organic solvent includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0017] Preferably, the mixing temperature is 20 to 150° C. and the mixing time is 8 to 60 hours.
[0018] Preferably, the film forming comprises: casting and casting the mixed mixture and then drying it.
[0019] The present invention also provides the use of the PEO-PAN based polymer electrolyte membrane described in the above technical solution or the PEO-PAN based polymer electrolyte membrane prepared by the preparation method described in the above technical solution in a lithium battery.
[0020] The present invention promotes the dissociation of lithium salts in the PEO-PAN-based polymer electrolyte membrane by introducing acidic organic boric acid substances, thereby promoting rapid and efficient transmission of lithium ions in the PEO-PAN-based polymer electrolyte membrane at room temperature, thereby improving the conductivity of the PEO-PAN-based polymer electrolyte membrane.
[0021] Greatly improve the critical current density of polyethylene oxide (PEO) organic-inorganic composite solid active filler and greatly extend the cycle time of lithium symmetric batteries. DETAILED DESCRIPTION
[0022] The present invention provides a PEO-PAN based polymer electrolyte membrane, comprising the following components: PEO, PAN, lithium salt, active filler and acidic organic boric acid substances;
[0023] The mass ratio of PEO to lithium salt is (1-20):1;
[0024] The mass ratio of PEO to PAN is (1-25):1;
[0025] The mass ratio of the total mass of PEO and lithium salt to the mass of the active filler is (1-40):1;
[0026] The mass ratio of the total mass of the PEO and the lithium salt to the acidic organic boric acid substance is (1-40):1.
[0027] In the present invention, the mass ratio of PEO to lithium salt is (1-20):1. In a specific embodiment of the present invention, the mass ratio of PEO to lithium salt can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1; the lithium salt preferably includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
[0028] In the present invention, the mass ratio of PEO to PAN is (1-25):1. In a specific embodiment of the present invention, the mass ratio of PEO to PAN can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1 or 25:1.
[0029] In the present invention, the mass ratio of the total mass of PEO and lithium salt to the active filler is (1-40):1. In a specific embodiment of the present invention, the mass ratio of the total mass of PEO and lithium salt to the active filler can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1 :1, 27:1, 28:1, 29:1, 30:1, 32:1, 34:1, 36:1, 38:1 or 40:1; the active filler preferably includes lithium element; the active filler preferably includes one or more of lithium lanthanum zirconium tantalum oxide (LLZTO), lithium indium chloride (Li3InCl6), lithium yttrium chloride (Li3YCl6), lithium zirconium chloride (Li2ZrCl6), lithium tantalum chloride (LiTaCl6), lithium aluminum titanium phosphide (LATP), lithium aluminum germanium phosphate (LAGP), lithium aluminum germanium phosphide (LGTP) and lithium phosphorus sulfur chloride (LPSCl).
[0030] The introduction of lithium salts and active fillers can effectively improve the ionic conductivity and mechanical strength of PEO-PAN-based polymer electrolyte membranes at near room temperature.
[0031] In the present invention, the mass ratio of the total mass of the PEO and the lithium salt to the acidic organic boronic acid substance is (1-40):1. In a specific embodiment of the present invention, the mass ratio of the total mass of the PEO and the lithium salt to the acidic organic boronic acid substance can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1. 1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 32:1, 34:1, 36:1, 38:1 or 40:1; the acidic organic boronic acid substances preferably include 4-(morpholine-4-carbonyl)phenylboronic acid, 4-pyridineboronic acid, 3-acetylphenylboronic acid Boric acid, 4-methyl-1-naphthylboronic acid, catecholborane, 3-pyrrolidineboronic acid, benzofuran-2-boric acid, dibenzofuran-4-boric acid, 2-benzylthiophenylboronic acid, 3-aminophenylboronic acid hemisulfate, cyclohexene-1-ylboric acid, tetrahydropyran-4-boric acid, 3-mercaptophenylboronic acid, borane-N,N-diethylaniline, pyrimidine-4-boric acid, pyrazine-2-boric acid, selenophene-2-boric acid, m-aminophenylboronic acid, 2-anthraceneboric acid , 2-cyanophenylboronic acid, 4-(piperidine-1-carbonyl)phenylboronic acid, indazole-7-boric acid, 1H-pyrazole-4-boric acid, dibutylboron trifluoromethanesulfonate, 4-methylthiophene-2-boric acid, isoquinoline-6-boric acid, 4-benzyloxyphenylboric acid, 5-bromo-2-thiopheneboric acid, 6-ethoxy-2-naphthaleneboric acid, 2-methyl-4-pyridineboric acid, divaleryldiboron and one or more of 1H-imidazol-2-ylborate hydrochloride.
[0032] The introduction of lithium salts and acidic organic boric acid substances can in situ form a strong, low-impedance interfacial layer with an inorganic phase, significantly improving the interfacial compatibility between PEO-PAN-based polymer electrolyte membranes and lithium metal.
[0033] The present invention also provides a method for preparing the PEO-PAN based polymer electrolyte membrane according to the above technical solution, comprising the following steps:
[0034] The PEO, PAN, lithium salt, active filler, acidic organic boric acid substance and organic solvent are mixed and then film-formed to obtain the PEO-PAN based polymer electrolyte membrane.
[0035] In the present invention, the organic solvent preferably includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
[0036] In the present invention, the mixing temperature is preferably 20-150°C, and the time is preferably 8-60h; in a specific embodiment of the present invention, the mixing temperature can be 20°C, 30°C, 50°C, 70°C, 80°C, 90°C, 110°C, 130°C or 150°C, and the time can be 8h, 16h, 24h, 30h, 36h, 40h, 45h, 50h or 60h.
[0037] In the present invention, the film forming preferably includes: casting and casting the mixed mixture and then drying it.
[0038] In the present invention, the drying temperature is preferably 20-100°C, and the time is preferably 2-48h; in a specific embodiment of the present invention, the drying temperature can be 20°C, 30°C, 50°C, 70°C, 80°C or 100°C, and the time can be 2h, 4h, 8h, 16h, 24h, 30h, 36h, 40h or 48h.
[0039] The present invention also provides the use of the PEO-PAN based polymer electrolyte membrane described in the above technical solution or the PEO-PAN based polymer electrolyte membrane prepared by the preparation method described in the above technical solution in a lithium battery.
[0040] The PEO-PAN based polymer electrolyte membrane provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] The number average molecular weight of PEO used in the examples and comparative examples is 600,000; the number average molecular weight of PAN is 250,000;
[0042] In the embodiments and comparative examples, stable cycling means that the voltage and capacity remain unchanged.
[0043] Example 1
[0044] 5 g PEO, 2.5 g LiTFSI and 5 g PAN were weighed respectively, and then 0.2 g Li2ZrCl6 powder and 0.2 g 4-(morpholine-4-carbonyl)phenylboronic acid were added, and then DMSO was added. The mixture was heated and stirred at 80 °C for 36 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 36 h to obtain a PEO-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.17×10 -5 S / cm, the interfacial impedance is 457.6Ω, and its lithium symmetric half-cell is 0.1mA cm -2 The current density can be stably cycled for 60 hours.
[0045] Example 2
[0046] 20 g PEO, 1 g LiBOB and 0.8 g PAN were weighed respectively, and then 10 g Li3InCl6 powder and 5 g 4-methyl-1-naphthaleneboric acid were added, and then NMP was added. The mixture was heated and stirred at 80 °C for 18 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 80 °C for 24 h to obtain a PEO-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 4.27×10 -5 S / cm, the interface impedance is 378.4Ω, and its lithium symmetric half-cell is 0.1mAcm -2 The current density can be stably cycled for 110 hours.
[0047] Example 3
[0048] 5 g PEO, 1 g LiODFB and 2.5 g PAN were weighed respectively, and then 0.6 g LATP powder and 1 g catechol borane were added, and then DMAC was added. The mixture was heated and stirred at 45 °C for 40 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 36 h to obtain a PEO-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 7.37×10 -5 S / cm, the interfacial impedance is 309.3Ω, and its lithium symmetric half-cell is 0.1mA cm -2 The current density can be stably cycled for 200 h.
[0049] Example 4
[0050] 6 g PEO, 1 g LiFSI and 2 g PAN were weighed respectively, and then 1 g LAGP powder and 1 g dibenzofuran-4-boric acid were added, followed by acetonitrile. The mixture was heated and stirred at 45 °C for 24 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 18 h to obtain a PEO-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 1.7×10 -4 S / cm, the interface impedance is 212.9Ω, and its lithium symmetric half-cell is 0.1mAcm -2 The current density can be stably cycled for 200 h.
[0051] Example 5
[0052] 6 g PEO, 6 g LiPO2F2 and 1.5 g PAN were weighed respectively, and then 1.2 g LLZTO powder and 1 g dibenzofuran-4-boric acid were added, and then DMSO was added. The mixture was heated and stirred at 45 °C for 24 h to obtain a uniformly mixed slurry, which was then cast in a polytetrafluoroethylene mold and vacuum dried at 60 °C for 18 h to obtain a PEO-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 5.7×10 -4 S / cm, the interface impedance is 93.7Ω, and its lithium symmetric half-cell is 0.1mAcm -2 The current density can be stably cycled for 500 h.
[0053] Comparative Example 1
[0054] 6 g of polymethyl methacrylate (PMMA, number average molecular weight of 130000), 6 g of LiPO2F2 and 1.5 g of PAN were weighed respectively, and then 1.2 g of LLZTO powder and 1 g of dibenzofuran-4-boric acid were added, and then DMSO was added. The mixture was heated and stirred at 45 °C for 24 h to obtain a uniformly mixed slurry, which was then cast on a polytetrafluoroethylene mold and vacuum dried at 60 °C for 18 h to obtain a PVDF-PAN-based polymer electrolyte membrane with a thickness of 270 μm. After cutting, its lithium ion conductivity was tested, and its lithium ion conductivity was 6.7×10- 6 S / cm, the interfacial impedance is 567.3Ω, and its lithium symmetric half-cell is 0.1mA cm -2 The current density can be stably cycled for 30 hours.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A PEO-PAN based polymer electrolyte membrane, characterized in that: The invention comprises the following components: PEO, PAN, lithium salt, active filler and acidic organic boric acid substances; The mass ratio of PEO to lithium salt is (1-20):1; The mass ratio of PEO to PAN is (1-25):1; The mass ratio of the total mass of PEO and lithium salt to the mass of the active filler is (1-40):1; The mass ratio of the total mass of the PEO and the lithium salt to the acidic organic boric acid substance is (1-40):
1.
2. The PEO-PAN based polymer electrolyte membrane according to claim 1, characterized in that: The lithium salt includes one or more of LiFSI, LiTFSI, LiBOB, LiODFB, LiBF4, LiPO2F2 and LiAsF6.
3. The PEO-PAN based polymer electrolyte membrane according to claim 1, characterized in that: The active filler includes lithium element.
4. The PEO-PAN based polymer electrolyte membrane according to claim 1 or 3, characterized in that: The active filler includes one or more of lithium lanthanum zirconium tantalum oxide, lithium indium chloride, lithium yttrium chloride, lithium zirconium chloride, lithium tantalum chloride, lithium aluminum titanium phosphide, lithium aluminum germanium phosphate, lithium aluminum germanium phosphide and lithium phosphorus sulfur chlorine.
5. The PEO-PAN based polymer electrolyte membrane according to claim 1, characterized in that: The acidic organic boronic acid substances include 4-(morpholine-4-carbonyl)phenylboronic acid, 4-pyridineboronic acid, 3-alkynephenylboronic acid, 4-methyl-1-naphthaleneboronic acid, catecholborane, 3-pyrrolidineboronic acid, benzofuran-2-boric acid, dibenzofuran-4-boric acid, 2-benzylthiophenylboronic acid, 3-aminophenylboronic acid hemisulfate, cyclohexene-1-ylboric acid, tetrahydropyran 4-boric acid, 3-mercaptophenylboric acid, borane-N,N-diethylaniline, pyrimidine-4-boric acid, pyrazine-2-boric acid , selenophene-2-boric acid, m-aminophenylboric acid, 2-anthraceneboric acid, 2-cyanophenylboric acid, 4-(piperidine-1-carbonyl)phenylboric acid, indazole-7-boric acid, 1H-pyrazole-4-boric acid, trifluoromethanesulfonate dibutylboron, 4-methylthiophene-2-boric acid, isoquinoline-6-boric acid, 4-benzyloxyphenylboric acid, 5-bromo-2-thiopheneboric acid, 6-ethoxy-2-naphthaleneboric acid, 2-methyl-4-pyridineboric acid, divaleryldiboron and one or more of 1H-imidazol-2-ylboric acid hydrochloride.
6. The method for preparing a PEO-PAN based polymer electrolyte membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: The PEO, PAN, lithium salt, active filler, acidic organic boric acid substance and organic solvent are mixed and then film-formed to obtain the PEO-PAN based polymer electrolyte membrane.
7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of acetonitrile, dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.
8. The preparation method according to claim 6, characterized in that: The mixing temperature is 20-150° C. and the mixing time is 8-60 hours.
9. The preparation method according to claim 6, characterized in that: The film forming comprises: casting and casting the mixed mixture and then drying it.
10. Use of the PEO-PAN based polymer electrolyte membrane according to any one of claims 1 to 5 or the PEO-PAN based polymer electrolyte membrane prepared by the preparation method according to any one of claims 6 to 9 in lithium batteries.